Distribusi Dalam Ekonomi Islam - Amiroh Rona Zakiyah; Fika Lestari; Rohimin; Ramedlon (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Distribution in Islam is a fundamental concept that emphasizes economic justice, equitable welfare, and the prevention of wealth concentration among specific groups. This study aims to analyze the Islamic perspective on distribution by employing a literature review supported by Qur’anic and Prophetic foundations. The findings indicate that Islamic distribution encompasses two key dimensions: the distribution of goods and services through lawful market mechanisms, and the distribution of income through Sharī‘ah-based instruments such as zakat, infaq, sadaqah, gifts, and inheritance. Foundational principles including the prohibition of riba and gharar, the concept of ownership as a trust, and the obligation to uphold social justice play a crucial role in regulating the flow of wealth. Comparisons with capitalist and socialist systems reveal that the Islamic model provides a balanced structure that integrates individual freedom with social responsibility. Ethical guidelines demanding transparency, honesty, and spiritual orientation further strengthen the system’s effectiveness. Thus, the Islamic distribution framework offers significant contributions to developing just and applicable economic theories for contemporary economic challenges.